2005
DOI: 10.4049/jimmunol.175.12.8320
|View full text |Cite
|
Sign up to set email alerts
|

Topical Superantigen Exposure Induces Epidermal Accumulation of CD8+ T Cells, a Mixed Th1/Th2-Type Dermatitis and Vigorous Production of IgE Antibodies in the Murine Model of Atopic Dermatitis

Abstract: Patients with atopic dermatitis (AD) have repeated cutaneous exposure to both environmental allergens and superantigen-producing strains of Staphylococcus aureus. We used a murine model of AD to investigate the role of staphylococcal enterotoxin B (SEB) in the modulation of allergen-induced skin inflammation. Mice were topically exposed to SEB, OVA, a combination of OVA and SEB (OVA/SEB), or PBS. Topical SEB and OVA/SEB exposure induced epidermal accumulation of CD8+ T cells and TCRVβ8+ cells in contrast to OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…Our data are reminiscent to previous studies in human AD showing that, although CD4 ϩ T cells predominated in AD skin lesions, T cells infiltrating the epidermis were almost exclusively CD8 ϩ T cells (12). Along these lines, studies in mouse models of AD reported that allergen challenge is associated with epidermal recruitment of CD8 ϩ T cells (25), which is dramatically enhanced by coexposure to the superantigen staphylococcal enterotoxin B (26). However, only a few CD8 ϩ T cells, compared with CD4 ϩ T cells, were detected in the skin in these studies probably because of the time at which T cell infiltration was analyzed.…”
Section: Discussionsupporting
confidence: 63%
“…Our data are reminiscent to previous studies in human AD showing that, although CD4 ϩ T cells predominated in AD skin lesions, T cells infiltrating the epidermis were almost exclusively CD8 ϩ T cells (12). Along these lines, studies in mouse models of AD reported that allergen challenge is associated with epidermal recruitment of CD8 ϩ T cells (25), which is dramatically enhanced by coexposure to the superantigen staphylococcal enterotoxin B (26). However, only a few CD8 ϩ T cells, compared with CD4 ϩ T cells, were detected in the skin in these studies probably because of the time at which T cell infiltration was analyzed.…”
Section: Discussionsupporting
confidence: 63%
“…The colonization of S. aureus on the skin plays an important part in the pathology of AD [16,17,18,19]. Various staphylococcal superantigens have been analyzed for their potential to intensify AD or other skin diseases [16,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcal superantigen has been documented to reduce regulatory T cell activity in humans (22) and to confer T cell steroid resistance (23), but these studies have not examined the influence of superantigen on allergen-specific T cell responses. A murine study showed that combined staphylococcal enterotoxin B (SEB) and ovalbumin application to the skin increased ovalbumin-specific IgE, but again the role of specific T cells has not been addressed (24). Using house dust mite-derived Der p 1 as the model allergen, we sought to test the hypothesis that S. aureus superantigen influences the allergenspecific T cell response.…”
Section: Atopy ͉ T Cells ͉ Keratinocytes ͉ Staphylococcusmentioning
confidence: 99%